The Life-Giving Myth. - Hocart, A. M. (Taylor and Francis, 2013)
Myths are the expression of a form of knowledge essential to life. Including mainly previously unpublished work by A.M. Hocart the book examines such issues as: Why a queen should not have been married before; why a guest is sacred; why people are believed to have been turned into stone; how money originated. These issues are considered as part of a socio-religious complex embraced in many parts of the world, both East and West. (There are chapters on the UK, India, Sri Lanka, Africa, Fiji, Egypt, and Ancient Greece).